Shwadamstradi Ghrita Uttarbasti the Ayurvedic Treatment of Urethral Stricture - Varsadiya, Akash; Sharma, Rajeshkumar; Kanani, Dipa (Asian Journal of Pharmaceutical Research and Development, 2024)
In Ayurveda, Acharya Sushrut mentioned miraculous treatment for urethral stricture or mentioned as Mutrakruccha in Ayurvedic classical texts.Which briefly means difficulty in micturition. Mutrakruccha can be correlated withUrethral stricture due to the similarity between the symptoms. Many surgical and non-surgical treatments are available in modern medical science. Still, dueto thehigh recurrence and huge financial burden on the health system, Ayurvedic treatment Uttarbasti is showing promising results in the management of Urethral Stricture.Uttarbasti is the delivery of therapeutic oil or decoction via the urethra or vaginal channel.Urethral strictures can result from inflammatory, ischemic, or traumatic processes. These processes lead to scar tissue formation; scar tissue contracts and reduces the caliber of the urethral lumen, causing resistance to the flow of urine. Urethral strictures arise from various causes and can result in a range of manifestations, from an asymptomatic presentation to severe discomfort secondary to urinary retention. Retrograde urethrogram (RUG) is the main diagnostic tool to find urethral stricture and help find the length of the stricture. There is no modernmedical-science treatment for urethral stricture disease, however, urinary tract infections (UTIs) should be adequately treated before surgical intervention. Surgical treatment of urethral stricture disease is indicated when the patient has severe voiding symptoms, bladder calculi, increased postvoid residual, or urinary tract infection or when conservative management fails. Due to the high recurrence rate of surgical intervention in Urethral stricture non-invasive treatment such as Uttarbasti is always appreciated.